Research of Full-posture Workspace and Its Characteristic of 3-RRR Planar Parallel Robot - Cui Jiankun; Yu Jiajun; Cao Liya (Jixie chuandong)
A new representation method of the workspace of a planar parallel manipulator is presented.Taking the 3 RRR plane parallel robot as an example,according to the iterative search method,the inverse solution equation is used as the discriminant,and the circular search of workspace is carried out. After the data processing,the three-dimensional display of the full-posture workspace of planar parallel manipulator is obtained,and its characteristics are studied. On this basis,the reachable workspace is obtained and the working space does not exist empty pole length ratio.